Matter, Form and Meaning in Architecture: A Cross-Cultural Reading of Parliament Buildings - Dilaveroğlu, Büşra (Emerald Publishing Limited, 2025)
Purpose – Seeking meaning in architecture has been an ever-present strand in architectural theory, whose reverberations sound in critical considerations of the complicated interdependence among matter, form and meaning conveyed in designed environments. The interdependence is especially evident in public architecture, where buildings pass beyond functional significance to become bodily expressions of administration, culture and national identity. Of these, parliamentary buildings hold a particular significance in their designs since they reflect the political aspirations, ideological models and social values of their eras. Designed as a vocabulary of governance, these buildings articulate the prevailing political ethos, encoding meaning through their materiality, spatial composition and architectural language. This study explores the semiotic dimensions of parliamentary buildings across three distinct geographical contexts, analyzing how their design is crafted to convey meaning. Design/methodology/approach – This study examines the semiotic dimensions of three parliamentary buildings, analyzing how architectural elements – form, materiality, ormamentation and spatial arrangement – encode and communicate meaning. Using semiology as a methodological framework, it explores three parliament buildings in distinct geographies, historical contexts and political systems: the Scottish Parliament (Deconstructivism), the Welsh Parliament (Contemporary Architecture) and the Turkish Parliament (Neo- Classicism). Findings – The findings reveal that architectural signs and their signifiers are given meaning according to their respective eras’ ideological foundations and stylistic preferences. Certain elements, such as the geography and historical context of a building, are semiotically reflected through material choices, serving as tangible connections to place and heritage. In contrast, architectural styles and their symbolic meanings are more explicitly influenced by the prevailing ideologies and architectural trends of the time, shaping the symbolic significance and interpretation of architectural signs. Originality/value – This study provides a novel framework for understanding how ideological and political identities are embedded in built environments by applying semiotic theory to three parliament buildings in different geographies with different stylistic approaches. It offers insights into the constructed relationship between architecture and governance, contributing to architectural theory and practice.
Keywords: Architectural Meaning; Semiotic Analysis; Parliament Buildings; Ideological Symbolism